Genome-wide identification and analysis of ERF transcription factors related to abiotic stress responses in Nelumbo nucifera - Yingchun Xu; Junnan Jiang; Lihong Zeng; Huan Liu; Qijiang Jin; Ping Zhou; Yanjie Wang (BMC Plant Biology)
Abstract Background Ethylene-responsive factor (ERF) transcription factors belong to the APETALA2/ERF (AP2/ERF) superfamily, and play crucial roles in plant development process and stress responses. However, the function of ERF proteins (especially for their role in response to abiotic stresses) remains scarce in Nelumbo nucifera, which is an important aquatic plant with high ornamental, economic, and ecological values. Results A total of 107 ERF genes were identified from the N. nucifera genome, and phylogenetic analysis classified these genes into 11 groups. The NnERF genes in the same group exhibited similar gene structure and conserved motifs, and they were unevenly distributed across the 8 chromosomes, with three pairs of tandem duplications and 21 pairs of segmental duplications. Synteny analysis revealed 44 and 39 of NnERF genes were orthologous to those in Arabidopsis thaliana and Oryza sativa, respectively. Tissue-specific expression patterns analysis of NnERF showed that 26 NnERF genes were expressed in all tested tissues, in which five genes exhibited high expression levels. Furthermore, 16 NnERF genes were selected for exploring their responses to different abiotic stresses, including cold, salt, drought, and Cd stresses. qRT-PCR analysis revealed that all these 16 investigated genes were regulated by at least one stress treatment, and 12 genes responded to all the stress treatments with different expression patterns or levels, suggesting their potential roles in diverse abiotic stress tolerance of N. nucifera. Additionally, two representative stress-related NnERFs (Nn3g19628 and Nn1g06033) were confirmed to be nuclear-localized proteins and displayed transcriptional activation. Conclusions In this study, we conducted a genome-wide identification and analysis of NnERF gene family related to abiotic stress responses in N. nucifera, which provides valuable information for further functional validation of these genes in stress responses, and forms a foundation for stress tolerance breeding in N. nucifera and other aquatic ornamental plants.